Aplicação de processo oxidativo avançado (H2O2/UV) em efluente de uma indústria de embalagens - Rocha, Antônio Herbert Quintino (2010)
The high industrial growth, driven by high consumption due to population growth and better income, is an indicator of industry type, the packaging industry. Effluents produced from packing manufacture in the print works industry carry strong color. If the effluent is disposed in the environment, it can cause esthetical problems besides significant environmental impacts causing serious damage to the photosynthesis process in the water sources. The objective of this study is to remove the color of an industrial effluent from a packing plant using an advanced oxidation process (AOP), after it has been treated by a physic-chemical process. He effluent samples were subjected to the treatment proposed by a photoreactor of 0,5L, with power of 210W. The samples (10,0L each sample) were circulated during 8 hours, when samples were taken within 1, 2, 3, 4, 5, 6, 7 and 8h. In a first stage was established to a best operational adjustment, by varying of the flow (4,0L/min e 1,0L/min) as also as the dosage of H2O2 (1,0%, 0,5% and 0,25%). The removal of the color was achieved in all variations of dosages applied, but the test with 1,0% H2O2 using the flow of 1,0L/min showed a removal of color quickly (short time of circulation) and a significant removal of DQO in just four hours of circulation. The results reveal that the POA (H2O2/UV) is effective in removing color from effluents from the packaging industry that perform printing. However studies should be performed to reduce deployment costs for a full-scale system.